Effect of plastic anisotropy on microscale ductile fracture and microformability of stainless steel foil. (November 2018) - Meng, B.; Zhang, Y.Y.; Cheng, C.; Han, J.Q.; Wan, M.
Highlights: The anisotropy of metal foil is significantly enhanced with decreasing λ ratio. Deviation of strain path is worsened at microscale and sensitive to stress state. The shape of FLC for 200 and 100 μm thick foils differs from the common V-type. The FLC tends to approach FFLC at microscale level. Abstract: The thin foil undergoing extensive plastic deformation during the rolling process usually exhibits a significant anisotropy. In microforming, due to the downscaling effect, the influence of plastic anisotropy on ductile fracture behavior and material formability is size-dependent. To clarify the interaction of size effect and plastic anisotropy on the formability of thin foil, the tensile tests and forming limit experiments of SUS304 foils with different thicknesses and grain sizes were performed. It is found that the deformation behavior changes from polycrystalline to the single crystal as the reduction of λ, the number of grains across the thickness direction. This transformation significantly affects the fracture behavior including limit strain, ultimate stress, and fracture mechanism. Furthermore, the difference in fracture behavior among diverse deformation orientations is aggravated with the reduction of foil thickness and the increase of grain size. Due to the interaction of size effect and plastic anisotropy, the microformability of metal foils is shifted down with the reduction of λ, and the severe scatter in the forming limit curve (FLC) of 20 μm thick foil is observed. Besides, the deviation of strain path from linearity is increased with decreasing λ, which is caused by the coupled effect of the intensified anisotropy and the declined compatible deformation capability. Unlike the common V-type FLC, the microscale FLCs of the specimens with the thicknesses of 200 and 100 μm are characterized by a continued drop of the limit strain along the strain paths from uniaxial tension, planar strain to biaxial stretching. The phenomenon is ascribed to the multiple effects of the deviation of strain path, material anisotropy and the transformation of fracture pattern at the microscale level. Graphical abstract: